Processing of thermoplastic elastomers (TPE) by in-situ ground tire rubber (GTR) vulcanization using waste ethylene-vinyl-acetate (wEVA) and dicumyl peroxide (DCP) (2024)
Tire rubber waste (TRW) is a complex mixture of materials, such as rubbers, steel, textile fibers, carbon black, and other additives. Its polluting capacity is a severe environmental problem, especially in landfills and waste management processes. As a practical solution to mitigate TRW’s environmental impact, thermoplastic elastomers (TPE) commonly reuse the ground tire rubber (GTR). This work presents an in-situ devulcanization of ground tire rubber (DGTR) and re-vulcanization of devulcanized ground tire rubber using dicumyl peroxide (DCP) and waste ethylene-vinyl-acetate (wEVA). The GTR was devulcanized through thermo-mechanical action and then blended with waste ethylene-vinyl-acetate (wEVA) and dicumyl peroxide (DCP) to produce the thermoplastic elastomer (TPE). This blending process was monitored using a torque rheometer and analyzed with differential scanning calorimetry (DSC) to evaluate the crosslinking reactions and kinetic behavior. The results indicated that in-situ vulcanization took place within the rheometer mixing chamber, evidenced by an increase in torque. DSC analysis of the DGTR-DCP-wEVA system confirmed the curing reaction prior to vulcanization. The resulting in-situ vulcanized TPE ensures improved component adhesion. This research offers practical insights into a scalable, non-advanced process for local plastics industries in developing countries to incorporate vulcanized TPEs, thereby enhancing their knowledge and understanding of this innovative approach.